Prescription Profile of Antibiotic Drugs Post Excision Biopsy of Oral Soft Tissue Disease in Palembang - Nadhila Apriadhanti; Nita Parisa; Siti Rusdiana Puspa Dewi (HM Publisher, 2021)
Backgroud An excisional biopsy is one of the surgical treatments given to cases ofsmall benign tumors in the soft tissues of the oral cavity. Antibiotics are prescribedby dentists as a follow-up therapy after excisional biopsy to prevent bacterialinfection. The purpose of this study was to determine the profile of antibiotic drugprescription after excision biopsy of oral soft tissue disease by dentists in Palembang.Methods This type of research is descriptive observational with a survey method.The research was carried out by distributing questionnaires to 40 dentists anddental specialists in Palembang who had performed excision biopsy treatment fororal soft tissue disease. Result The results showed that the antibiotic prescriptionof amoxicillin was 55%, the combination of amoxicillin and clavulanic acid was17.5%, and clindamycin was 12.5%. The cases found in this study were epulis57.5%, mucocele 30%, and traumatic fibroma 10%. Conclusion It can be concludedthat the antibiotic most often prescribed by dentists in Palembang after excisionbiopsy treatment was amoxicillin and the most common case was epulis.